Reliability and magnitude of mechanical variables assessed from unconstrained and constrained loaded countermovement jumps - Garcia-Ramos, A.; Jaric, S.; Pérez-Castilla, A.; Padial, P.; Feriche, B. (Sports Biomechanics, 2017)
AbstractThis study aimed to (1) assess the reliability of the force, velocity, and power output variables measured by a force plate and a linear velocity transducer (LVT) for both the unconstrained and constrained loaded countermovement jump (CMJ), and (2) examine the effect of both the CMJ type and the measurement method on the magnitudes of the same variables. Twenty-three men were tested on the free CMJ and the CMJ constrained by a Smith machine. Maximum values of force, velocity, and power were recorded by a force plate and by a LVT attached to a bar loaded by 17, 30, 45, 60, and 75kg. The reliability of all mechanical variables proved to be high (ICC>0.70; CV<10%) and similar for two CMJ types. However, force plate-derived measures displayed greater reliability than the LVT. The LVT also markedly overestimated the magnitudes of the mechanical variables, particularly at lower external loads. Therefore, although both jump types and both methods could be acceptable for routine testing, we recommend the force platform due to a higher reliability and more accurate magnitudes of the obtained variables. The unconstrained loaded CMJ could also be recommended due to the simpler equipment needed. ABSTRACT FROM AUTHOR